2004
DOI: 10.1163/1568560041352301
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory properties of BHUx, a polyherbal formulation to prevent atherosclerosis

Abstract: BHUx is a polyherbal formulation consisting of water-soluble fractions of five medicinal plants (Commiphora mukul, Terminalia arjuna, Boswellia serrata, Semecarpus anacardium and Strychnos nux vomica). The present study was undertaken to evaluate its antioxidant and antiinflammatory effects. BHUx, standardized by HPLC fingerprinting and filtered through 0.2 microm filter paper, was employed for different studies under in vivo and in vitro conditions. Under in vivo conditions, BHUx significantly reduced inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…Previously, BHUx, a modified formulation from Sandhika, has been shown to inhibit the activity of lipoxygenase-15 and cyclooxygenase-2 in a specific manner [34]. It has also shown significant protection against plaque development (Atherosclerosis) in the coronary artery [33], which is now suggested to be a progressive inflammatory disease [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, BHUx, a modified formulation from Sandhika, has been shown to inhibit the activity of lipoxygenase-15 and cyclooxygenase-2 in a specific manner [34]. It has also shown significant protection against plaque development (Atherosclerosis) in the coronary artery [33], which is now suggested to be a progressive inflammatory disease [38].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have reported that BHUx, a patented polyherbal formulation, prevents the diet-induced atherosclerosis in rabbits [33]. It acts through antiinflammatory pathways, specifically by inhibition of cyclooxygenase-2, lipoxygenase-15 and by its potent antioxidant property [34]. Since BHUx was originally derived from Sandhika, which is already in clinical use for the last 20 years for the management of arthritis [35], we investigated the role of Sandhika on LPS-induced changes in the calcium nodule formation in MC3T3-E1 osteoblastic like cells.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, anti-ulcerogenic activity of aerial parts has been reported (Araujo et al, 2006). A new cytotoxic resorcinol derivative was isolated from this plant (L贸pez et al, 2005) To our knowledge, there are no pharmacological studies that evaluate the anti-inflammatory potential of Lithrea molleoides but it has been reported that other species of Anacardiaceae such as Mangifera indica (Kn枚dler et al, 2008), Semecarpus anacardium (Tripathi et al, 2004), Schinus terebinthifolius (de Carvalho et al, 2003) and Anacardium occidentale (Ojewole, 2004) present anti-inflammatory effects. Moreover, flavonoids with antiinflammatory activity were isolated from different members of this family, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is a patented polyherbal formulation (12), simultaneously targeting oxidative stress and inflammation (13). It consists of a specific water-soluble extract of five medicinal plants, which are time tested and have been used in the ayurvedic system of medicine for many centuries (14).…”
Section: Introductionmentioning
confidence: 99%
“…CaCO 3 (Shankha Bhasma) has been added to the finished product to reduce gastric irritation, if any. The finished product has been standardized by using high-performance liquid chromatography (HPLC) and thin-layer chromatography (TLC) fingerprinting (13). …”
Section: Introductionmentioning
confidence: 99%